P27 Personal allergen exposures are increased by changes in sleep position and improved by temperature-controlled laminar airflow. (16th November 2010) - Gore, RB; Boyle, RJ; Hanna, H; Custovic, A; Gore, C; Svensson, P; Warner, JO
Abstract : Introduction and Objectives: Aeroallergens are released directly from bedding into the breathing zone, and contribute importantly to asthma symptoms. Adults change their sleep position between 3 and 45 times per night. The effect of these turns on inhaled particulate exposures is unknown. We aimed to investigate the effects of changing position on breathing zone particulate exposures and the effect of a novel Temperature-controlled Laminar Airflow (TLA) device on reducing such exposures. Methods: A simulated bedroom was constructed containing bedding from a cat owner. Five healthy volunteers lay recumbent under an active and an inactive TLA device for 175 min. Volunteers made scheduled turns in bed to simulate normal sleep. Real-time total particle levels (≥0·5 μm diametre) within the breathing zone were measured by laser particle counting. Inhaled cat allergen exposure was measured by nasal air sampling. Time series analysis was used to evaluate changes in particulate exposures with turning. Results: A greater proportion of larger particles than smaller ones were disturbed by turning over (F=20.6, df=5, p<0.001). With the TLA switched off, 9% (95% CI 4 to 18) of total overhead particles >10 μm diametre were accounted for by turning over, compared with 0.2% (95% CI 0.07 to 0.5) of particles >0.5 μm diameter. TLA treatment reduced total particle numbers (size >0.5 μm) by 3010-fold (p<0.001) and significantly reduced the turn-associated increase for all particle sizes (Abstract P27 Figure 1, p<0.015). Similar turn-associated increases in nasal air sampler cat particle counts were seen. TLA treatment reduced nasal cat allergen exposures by sevenfold (p=0.043). Conclusions: Turning over in bed causes a significant increase in breathing zone exposures to particulates which are within the respirable size range. TLA treatment dramatically reduces overhead breathing zone total particulate exposures and also reduces nasal cat allergen exposure. TLA treatment attenuates the increase in particulate exposures caused by turning over. Treatments which result in better sleep quality and a reduced number of bodily turns may result in a reduction in personal breathing zone particulate exposures in bed.